Interference of ascorbic acid in the determination of hydroquinone using an amperometric enzyme biosensor based on carbon paste - Sýs, Milan; Pekec, Bruna; Kalcher, Kurt; Ribitsch, Volker; Feketeföldi, Birgit; Vytřas, Karel (Univerzita Pardubice, 2012)
The topic of this work deals with the interference of ascorbic acid in the determination of polyphenols with an amperometric biosensor containing tyrosinase. The sensor was prepared by covering carbon paste with a Nafion-film containing the enzyme. Hydroquinone (benzene-1,4-diol) is a polyphenolic compound which was used as a model one for amperometric measurements. Factors influencing the amperometric response were studied in detail. Optimized conditions for operating the biosensor in hydrodynamic amperometric mode were evaluated.
Keywords: ascorbic acid; biosensor; carbon paste electrode; hydrodynamic amperometry; hydroquinone; polyphenols; tyrosinase